Seeing with the Hands Blindness, Vision and Touch After Descartes - Paterson, Mark (Edinburgh University Press, 2022)
A literary, historical and philosophical discussion of attitudes to blindness by the sighted, and what the blind 'see'GBS_insertPreviewButtonPopup(['ISBN:9781474405317','ISBN:9781474405348','ISBN:9781474405331','ISBN:9781474405324']);The "man born blind restored to light" was one of two foundational myths of the Enlightenment, according to Foucault. With ophthalmic surgery in its infancy, the fascination with blindness and what the blind 'see' once their vision is restored remained largely hypothetical.